Gustatory Function and Salivary Flow Rate in Healthy Adults. (22nd December 2021) - Huang, Xiaobing; Guo, Yichen; Wei, Yongxiang
Abstract : Objectives/Hypothesis: In this study, we assessed gustatory function and whole‐mouth saliva in healthy adults and investigated the association between gustatory function, salivary flow rate (SFR), and dry mouth. Study Design: Descriptive clinical study. Methods: We recruited 413 participants who reported a normal sense of smell–taste, comprising 206 females and 207 males with an age range of 19 to 80 years. Taste scores were obtained using whole‐mouth tests to evaluate the gustatory function, SFR was assessed using the spitting method, and dry mouth was measured with the visual analog scale. Results: The total taste score (TTS) and SFR were significantly negatively correlated with age ( r taste  = −0.522, P  < .001; r SFR  = −0.200, P  < .001): TTS was significantly lower after the age of 50 and SFR decreased significantly after age 65. Women exhibited a significantly higher TTS than men ( P  < .001). However, there was no effect of sex on SFR. Dry mouth was negatively correlated with TTS ( r  = −0.223, P  < .01) and SFR ( r  = −0.218, P  < .01). Multiple regression analysis showed the independent variables of age, sex, and dry mouth predicted 34% of the variation in taste, while the independent variables of age and dry mouth predicted 6.1% of the variation in whole‐mouth saliva. TTS was not significantly correlated with the SFR in healthy adults ( r  = 0.094, P  = .056). Conclusions: Age and dry mouth are important factors affecting gustatory function and whole‐mouth saliva, with women exhibiting better taste sensitivity than men. Furthermore, there is no direct correlation between SFR and gustatory function in healthy adults. Level of Evidence: 3 Laryngoscope, 132:844–848, 2022